Acoustic performance of balconies having inhomogeneous ceiling surfaces on a roadside building facade. (November 2015) - Wang, Xu; Mao, Dongxing; Yu, Wuzhou; Jiang, Zaixiu
Abstract: Balconies provide noise screening effects in residential buildings even with the balcony door opened for natural ventilation. However, the screening effect of a balcony was found to be canceled due to the reflection from the ceiling. This paper describes a balcony whose ceiling is made from materials of inhomogeneous impedance which eliminates this drawback. The nonuniform impedance affects wave behavior by altering the direction of energy flux away from the region of a balcony as it reflects on the ceiling. A proposed realization of the balcony ceiling comprises a closely spaced array of progressively tuned hollow narrow tubes which create a phase gradient. The acoustic performance of a balcony with an inhomogeneous ceiling surface is examined theoretically by a ray-based model. All of the results predicted by the theory fit well with numerical simulations using a two-dimensional finite element method. Balconies with the proposed ceilings have the potential to be widely used in a roadside multi-residential building against the exterior traffic noise. Highlights: The inhomogenous ceiling successfully improved the shielding effect of a balcony. The inhomogeneous ceiling guided the energy flux away from the building facade. A ray-based model combining the image receiver and diffraction theories was presented. The realized balcony ceiling comprised a closely spaced array of hollow tubes.